PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA LARISSA AESTHETIC CENTER SEMARANG - Devi Hera Mustika, 13.05.51.0070; Yulianto, Heru (Students Journal of Economic and Management, 2017)
The magnitude of a persons need to take care of themselves to look beautiful and the growing lifestyle of women, ultimately give a big influence for the rapid development of beauty industry in Indonesia, especially in the form of beauty clinic business.This purpose of this study was to analysis the effect ofservice quality dimensions namely physical evidence, reliability, responsiveness, assurance, and empathy on customer satisfaction at Larissa Aesthetic Center Semarang.The population in this study is the customer who perform treatment at Larissa Aesthetic Center Semarang and aged over 18 years. The number of samples studied is as many as 100 people selected as respondents by using purposive sampling technique.Data collection methods used in this study is a questionnaire filled directly by the respondent. Analysis technique used in this research is validity test, reliability test,, multiple linear regression test, and hypothesis significance test. Data processing using SPSS Version 20. The results of this study indicate that the dimensions of service quality such as physical evidence, reliability, responsiveness, and assuranceempathy havenât an effect on customer satisfactionÂ  and empathy have aneffect on customer satisfaction.Â Keyword: Service Quality, Customer Satisfaction